Evaluation of changes in random blood glucose and body mass index during and after completion of chemotherapy in children with acute lymphoblastic leukemia - Kyong-Won Bang; Soo Young Seo; Jae Wook Lee; Pil-Sang Jang; Min Ho Jung; Nack-Gyun Chung; Bin Cho; Dae-Chul Jeong; Byung Kyu Suh; Hack-Ki Kim (Korean Pediatric Society, 2012)
PurposeImproved survival of patients with childhood acute lymphoblastic leukemia (ALL) has drawn attention to the potential for late consequences of previous treatments among survivors, including metabolic syndrome. In this study, we evaluated changes in 3 parameters, namely, random blood glucose, body mass index (BMI), and Z score for BMI (Z-BMI), in children with ALL during chemotherapy and after completion of treatment.MethodsPatients newly diagnosed with ALL from January, 2005 to December, 2008 at Saint Mary's Hospital, The Catholic University of Korea, who completed treatment with chemotherapy only were included (n=107). Random glucose, BMI, and Z-BMI were recorded at 5 intervals: at diagnosis, before maintenance treatment, at completion of maintenance treatment, and 6 and 12 months after completion of maintenance treatment. Similar analyses were conducted on 2 subcohorts based on ALL risk groups.ResultsFor random glucose, a paired comparison showed significantly lower levels at 12 months post-treatment compared to those at initial diagnosis (P<0.001) and before maintenance (P<0.001). The Z-BMI score was significantly higher before maintenance than at diagnosis (P<0.001), but decreased significantly at the end of treatment (P<0.001) and remained low at 6 months (P<0.001) and 12 months (P<0.001) post-treatment. Similar results were obtained upon analysis of risk group-based subcohorts.ConclusionFor a cohort of ALL patients treated without allogeneic transplantation or cranial irradiation, decrease in random glucose and Z-BMI after completion of chemotherapy does not indicate future glucose intolerance or obesity.